Agricultural biotechnology and transatlantic trade [ regulatory barriers to GM crops - Isaac, Grant (CABI Publishing, 2002)
Reviews the regulatory hurdles facing genetically modified crops in gaining access to the European Union and proposes a regulatory strategy to overcome such challenges